The Use of ChatGPT in English Language Learning: A Systematic Literature Review - Nur Hidayati; Erna Andriyanti; Novasa Adiyani (Tarling)
The integration of Artificial Intelligence (AI) in education has accelerated significantly, yet there remains a gap in systematic research exploring its role in English language learning. This systematic review examines 21 studies (2022–2024) on ChatGPT's role in English learning, focusing on its use by students and teachers, as well as its benefits and challenges. Following PRISMA guidelines, this review analyzes data from Scopus, ERIC, and Google Scholar using thematic analysis to identify key themes. The findings reveal that students employ ChatGPT for academic writing assistance, vocabulary development, and idea generation, while teachers leverage it for lesson planning, instructional material preparation, and student assessment. The advantages include enhanced motivation, improved writing proficiency, and personalized learning experiences. However, concerns such as over-reliance on AI, ethical dilemmas, and data privacy risks persist. This study underscores the potential of ChatGPT in fostering interactive and engaging language learning environments, advocating for a balanced integration of AI and traditional pedagogical approaches. The investigation of the sustained implication of ChatGPT use and approach to maximize the application in educational settings should be conducted for the future research.